2021
DOI: 10.3389/fnano.2021.680468
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy and Current Control of Magnetization in SrRuO3/SrTiO3 Heterostructures for Spin-Memristors

Abstract: Spintronics-based nonvolatile components in neuromorphic circuits offer the possibility of realizing novel functionalities at low power. Current-controlled electrical switching of magnetization is actively researched in this context. Complex oxide heterostructures with perpendicular magnetic anisotropy (PMA), consisting of SrRuO3 (SRO) grown on SrTiO3 (STO) are strong material contenders. Utilizing the crystal orientation, magnetic anisotropy in such simple heterostructures can be tuned to either exhibit a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, studies of SRO thin films grown on SrTiO 3 (STO) (001) substrates suggest a favorable perpendicular magnetic anisotropy with the easy axis normal to the film surface, along the [110] or direction. 11 A strong perpendicular anisotropy was also reported for SRO thin films on STO (110) substrates, 12,13 and systematic studies from Ziese 14 showed a biaxial magnetic anisotropy at low temperatures that rotate in different directions with increasing temperatures. This unique transformation of magnetic anisotropy in SRO is rooted in the crystalline anisotropy influenced by strong spin-orbit interactions and by the epitaxial strain imposed in the films.…”
mentioning
confidence: 62%
“…On the other hand, studies of SRO thin films grown on SrTiO 3 (STO) (001) substrates suggest a favorable perpendicular magnetic anisotropy with the easy axis normal to the film surface, along the [110] or direction. 11 A strong perpendicular anisotropy was also reported for SRO thin films on STO (110) substrates, 12,13 and systematic studies from Ziese 14 showed a biaxial magnetic anisotropy at low temperatures that rotate in different directions with increasing temperatures. This unique transformation of magnetic anisotropy in SRO is rooted in the crystalline anisotropy influenced by strong spin-orbit interactions and by the epitaxial strain imposed in the films.…”
mentioning
confidence: 62%
“…Applying an additional external magnetic field parallel to the electric current is a commonly used method for achieving the deterministic switching. 2 However, all-electric manipulation of magnetization is essential for practical device applications, and therefore, many studies on field-free switching methods are under investigation by exploring a material and systemic engineering as follows: antiferromagnetic layer and exchange bias, [10][11][12][13] competing spin current layer, 14 and magnetic trilayer, 15,16 tilted magnetic anisotropy, [17][18][19][20][21][22][23] structural asymmetry, 24,25 Rashba symmetry breaking. 26 Utilizing a chirality can be one efficient approach for achieving field-free SOT induced magnetization switching deterministically and it is firstly observed using chiral nanomagnet by Z. Luo et al 27 And then H. Wu et al confirms the possibility of field-free switching of perpendicular magnetization by chiral symmetry breaking in wedged system.…”
Section: Introductionmentioning
confidence: 99%